Sharing as sociomaterial practice: Car sharing and the material reconstitution of automobility. Issue 88 (January 2018) - Dowling, Robyn; Maalsen, Sophia; Kent, Jennifer L.
Abstract: Sharing has become one of the buzzwords of contemporary urban life and scholarship, as cities and social lives are transformed by the share economy and collaborative consumption. This paper advances critical analysis of sharing economies through an investigation of the ways in which objects are mobilized in the practice of sharing. Drawing on an empirical base of 35 interviews conducted with Sydney residents using car sharing as a form of transport, we explicate the material entanglements that constitute car sharing in order to highlight the complex intersections of the object being shared, the constellations of objects brought into the orbit of the practice, and the code that flows through each. Bringing together a material-focused analysis into conversation with the concepts of share economies as both performed and hybrid, we advance the concepts of sharing as a set of socio-material entanglements. We argue that the divergent spatialities and temporalities of objects and humans both hold together and tear apart the experiences of sharing, which in turn underpins car sharing's implications for the reconstitution of automobility.